NFATc1 and Tumor Associated Macrophages Affect Progression of Certain Subsets of Diffuse Large B Cell Lymphoma Non-GCB Subtypes - Krisna Murti; Muslina Muslina; Ika Kartika; Rachmat Hidayat; Ella Amalia (HM Publisher, 2021)
Introduction: Diffuse large B cell lymphoma (DLBCL) is the most common type of non-Hodgkin lymphoma among B cell lymphomas. The interaction of tumor cells with their microenvironment (tumor microenvironment, TME) leads to progressivity of malignancy. CD163 + macrophages known as components of TME. Nuclear factor of activated T cell (NFATc1) and MYC are important transcription factors in malignant transformation and progression. Therapeutic strategies were fast developed, nevertheless, efforts to decrease DLBCL morbidity and mortality are unsatisfied, therefore,new markers for prognosis and or therapeutic options of the patients are necessary. This study was aimed to investigate NFATc1 expression in DLBCL and its TME. Methods: Thirty-two paraffin blocks were selected then immunostained for expression of NFATc1, MYC, and CD163. Clinopathologic data i.e. ages, gender, and proliferation index Ki-67 were obtained. Data was analyzed by statistics Result: Positive expression of CD163 and NFATc1 was among 55% and 45% of cases respectively. All DLBCL cases in this study were non-GCB subtype and more patients were under 60 years (66%). Positive expression of CD163 was higher in males (69%) and in patients under 60 years (63%). Tissues positive for both NFATc1 and CD163 was observed higher among males and patients under 60 years. Conclusion: NFATc1 may affect development and or progression of certain subsets of DLBCL non-GCB subtype.